Homogeneous and heterogeneous catalysts for hydrogenation of CO2 to methanol under mild conditions. (9th March 2021) - Bai, Shao-Tao; De Smet, Gilles; Liao, Yuhe; Sun, Ruiyan; Zhou, Cheng; Beller, Matthias; Maes, Bert U. W.; Sels, Bert F.
Abstract : This review summarizes the concepts, mechanisms, drawbacks and challenges of the state-of-the-art catalysis for CO2 to MeOH under mild conditions. Thoughtful guidelines and principles for future research are presented and discussed. Abstract : In the context of a carbon neutral economy, catalytic CO2 hydrogenation to methanol is one crucial technology for CO2 mitigation providing solutions for manufacturing future fuels, chemicals, and materials. However, most of the presently known catalyst systems are used at temperatures over 220 °C, which limits the theoretical yield of methanol production due to the exothermic nature of this transformation. In this review, we summarize state-of-the-art catalysts, focusing on the rationales behind, for CO2 hydrogenation to methanol at temperatures lower than 170 °C. Both hydrogenation with homogeneous and heterogeneous catalysts is covered. Typically, additives (alcohols, amines or aminoalcohols) are used to transform CO2 into intermediates, which can further be reduced into methanol. In the first part, molecular catalysts are discussed, organized into: (1) monofunctional, (2) M/NH bifunctional, and (3) aromatization–dearomatization bifunctional molecular catalysts. In the second part, heterogeneous catalysts are elaborated, organized into: (1) metal/metal or metal/support, (2) active-site/N or active-site/OH bifunctional heterogeneous catalysts, and (3) cooperation of catalysts and additives in a tandem process via crucial intermediates. Although many insights have been gained in this transformation, in particular for molecular catalysts, the mechanisms in the presence of heterogeneous catalysts remain descriptive and insights unclear.